Impact of pregnancy and nutrition on oxidant⁄antioxidant balance in sheep and goats reared in South Sinai, Egypt - M. F. Nawito; Amal R. Abd El Hameed; A. S. A. Sosa; Karima Gh. M. Mahmoud (Veterinary World, 2016)
Aim: To monitor the effect of nutrition and pregnancy on oxidative status of animals under the arid condition of South Sinai. Materials and Methods: Blood samples were taken from two groups of animals: The first group retained in farm and fed on concentrate (high diet) and another group grazing natural forage (low diet). Each group was subdivided into pregnant and non-pregnant animals. Blood samples were assayed for their content of malondialdehyde (MDA), total antioxidant capacity (TAC), catalase (CAT), and superoxide dismutase (SOD) enzymes. Results: MDA level significantly increased in pregnant animals fed either concentrate or grazing low-quality forage and accompanied by a low level of TAC in pregnant grazing animals fed low-quality forage. The activity of CAT decreased in pregnant fed either concentrate or grazing and SOD significant decrease in the pregnant grazing group. These data suggested that the animals might have experienced some degree of oxidative stress and lipid peroxidation and indicating that redox homeostasis was impaired in those pregnant and specially fed on forage rations. Conclusion: Pregnancy constituted the most oxidative stress facing the grazing and concentrated diet feed sheep and goats under arid and saline conditions of Southern Sinai, Egypt.